On the variability of gender in Michif - Rosen, Nicole (Arborescences)

(untitled) (Département d'études françaises, Université de Toronto, 2020)
Michif, a critically endangered Metis mixed language still spoken by an estimated few dozen to a few hundred people across the Canadian Prairie provinces and British Columbia, makes use of two different gender systems: the French sex-based system contrasting masculine and feminine gender, and the Algonquian animacy-based system contrasting animate with inanimate gender. Systems distinguishing both animacy and sex-based gender are typologically rare, and the goal of this paper is to investigate both the productivity of Michif gender across the language, and the consistency (or put another way, the variability) of gender assignment in Michif. The data in this paper comes primarily from a reanalysis of previous research on Michif, with a goal to look at how variability plays a role in gender in Michif, and what this may tell us about gender more broadly. I suggest that we may want to treat gender as a variable phenomenon in the grammar more generally than is traditionally assumed.